Análisis del Programa de Fisiatría Oncológica para pacientes con cáncer de mama del Hospital San Rafael de Alajuela en el período comprendido entre mayo del 2015 a abril del 2016 - Laines Madrigal, Cindy 1983- (2016)
We intend to analyze the oncology physiatry program of the Hospital San Rafael de Alajuela using the data base of the consultation of patients witl:l breast cancer, attended from May 2015 to April 2016 who were treated with sorne of the surgical techniques that include Axillary lymph nade dissection. In addition, a comparative analysis of the ca re protocol used in this hospital was carried out with the ca re programs mentioned in the world literature. Methodology: The descriptive analysis was performed by calculating the averages of the variables defined in the instrument of statistical registration of the consultation of oncology physiatrics. Results: During this period SO patients were attended, of which 49 met the ínclusion criteria. Most women aged 60 to 69 years of age, housewives, the most freqaent histological type is infiltrating ductal carcinoma and the left breast is affected in most patients. The main surgical procedure was Modified Radical Mastectomy, more than half of the patients required adjuvant therapy (Radiotherapy and / or Chemotherapy) and the main complication derived from cancer treatment was omalgia. Recommendations: Within the care program should include measurement of body mass index, number of resected nades and implement the D.isabilities of Arm, Shoulder and Hand (DASH) questionnaire, the European Organization far Research and Treatment of Cancer scale EORTC QLQ- C30; And the EORTC specific breast cancer complement module QLQ-BR23; Which assess specific areas objectively and serve as parameters far futu-re comparative studies. In addition, it is suggested to include as part of the existing document the physiological interventions performed in the externa! consultation. An instrument was developed to benchmark the impact of rehabílitation on subsequent consultations.